Plant Genotype Influences Physicochemical Properties of Substrate as Well as Bacterial and Fungal Assemblages in the Rhizosphere of Balsam Poplar - Rheault, Karelle; Lachance, Denis; Morency, Marie-Josée; Thiffault, Évelyne; Guittonny, Marie; Isabel, Nathalie; Martineau, Christine; Séguin, Armand (Frontiers in Microbiology, 2020)
Abandoned unrestored mines are an important environmental issue since they typically remain unvegetated for decades, exposing vast amounts of mine waste to erosion. Several factors limit the revegetation of these sites, including extreme abiotic conditions and unfavorable biotic conditions. However, some pioneer tree species having high level of genetic diversity, such as balsam poplar (Populus balsamifera), are able to naturally colonize these sites and initiate plant succession. This suggests that some tree genotypes are likely more suited for acclimation to the conditions of mine wastes. In this study, two contrasting mine waste storage facilities (waste rock versus tailings) from the Abitibi region of Quebec (Canada), on which poplars have grown naturally, were selected. First, we assessed in situ the impact of vegetation presence on each type of mine wastes. The presence of balsam poplars improved soil health locally by improving physicochemical properties (e.g. higher nutrient content and pH) of the mine wastes and causing an important shift in their bacterial and fungal community compositions, going from lithotrophic communities that dominate mine waste environments to heterotrophic communities involved in nutrient cycling. Next, in a greenhouse experiment, ten genotypes of P. balsamifera collected on both mine sites and from a natural forest nearby were grown in these mine wastes. Tree growth was monitored during two growing seasons, after which the effect of genotype-by-environment interactions was assessed by measuring the physicochemical properties of the substrates and the changes in microbial communities, using a metabarcoding approach. Although substrate type was identified as the main driver of rhizosphere microbiome diversity and community structure, a significant effect of tree genotype was also detected, particularly for bacterial communities. Plant genotype also influenced aboveground tree growth and the physicochemical properties of the substrates. These results highlight the influence of balsam poplar genotype on the soil environment and the potential importance of tree genotype selection in the context of mine waste revegetation.